2009
DOI: 10.1007/s00198-009-0921-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of anti-depressants and the risk of fracture of the hip or femur

Abstract: The names of the second and third authors were given in the wrong order. The correct order of authors is as given above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…A reduced BMD in MS may be caused by the patient's immobility,7, 10 vitamin D deficiency,10 or use of GCs6, 7, 13 or antidepressants 23. Bone loss associated with physical inactivity can be explained by increased renal calcium losses, decreased gastrointestinal calcium absorption, secondary hyperparathyroidism, and increased bone turnover with depression of bone formation 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduced BMD in MS may be caused by the patient's immobility,7, 10 vitamin D deficiency,10 or use of GCs6, 7, 13 or antidepressants 23. Bone loss associated with physical inactivity can be explained by increased renal calcium losses, decreased gastrointestinal calcium absorption, secondary hyperparathyroidism, and increased bone turnover with depression of bone formation 7.…”
Section: Discussionmentioning
confidence: 99%
“…Potential confounders that were determined for a time‐dependent analysis included age, a history of chronic diseases (congestive heart failure, RA, cerebrovascular disease,19 inflammatory bowel disease, dementia, depression, epilepsy, and COPD20), as well as evidence of fatigue or visual disturbances 6 months before the start of a 30‐day interval. A prescription for orally or intravenously administered GCs,14, 21 statins,22 antiarrythmics, antidiabetics, antidepressants,23 antipsychotics,24 hypnotics/anxiolytics, asthma medication, anticonvulsants, hormone‐replacement therapy, vitamin D, levothyroxine, baclofen, or opioids (potencies equivalent to tramadol or higher) in the previous 6 months also were considered as potential confounders. The prescription of a medication was used as a proxy for use of that drug.…”
Section: Methodsmentioning
confidence: 99%
“…Antidepressants, notably selective serotonin reuptake inhibitors (SSRIs), have been associated with increased risk of femur or hip fracture . In observational studies, patients' exposure to SSRI medication may change over time; that is, physicians may stop SSRI therapy or switch to other classes of antidepressants because of adverse effects such as sexual dysfunction and drowsiness.…”
Section: Introductionmentioning
confidence: 99%
“…activities of daily living), which may impair the validity of study results. For example, several observational studies indicated an association between antidepressants use (mainly tricyclic antidepressants and selective serotonin re‐uptake inhibitors) and the risk of hip fracture. However, results from these studies are heterogeneous for many reasons .…”
Section: Introductionmentioning
confidence: 99%
“…For example, several observational studies indicated an association between antidepressants use (mainly tricyclic antidepressants and selective serotonin re‐uptake inhibitors) and the risk of hip fracture. However, results from these studies are heterogeneous for many reasons . Among them, confounding by unmeasured patient characteristics such as frailty, severity of depression, and lifestyle factors (e.g.…”
Section: Introductionmentioning
confidence: 99%